Development of a microelectrode array biosensor platform for the study of neuronal function - Ajetunmobi, Ayokunmi (Trinity College (Dublin, Ireland). Institute of Neuroscience, 2016)
The impact of brain disorders on the human population is significant, with neuropsychiatric illness, and in particular mood and psychotic disorders, contributing to over 25% of the 800 billion euro annual healthcare costs of neurological disorders across Europe. To combat this socio-economic challenge, novel therapeutic strategies are required that can identify sequences of events that underlie the processes of long-term synaptic function during post-natal development, in adult life and in the pathogenesis of neural diseases. Detecting this relationship between genes, synapse development and functional circuit maturation in disease models of neuronal development requires the analysis of multiple parameters in order to evaluate neurobiological activity, determine molecular biomarkers of the disease and identify novel therapeutic targets. However, current gold-standard techniques used to study the CNS have limitations that pose unique challenges to furthering our understanding of functional CNS development
Keywords: Neuroscience, Ph.D.; Ph.D. Trinity College Dublin, 2016